Manajemen Keluarga Sakinah pada Pasangan Suami Istri Difabel (Penelitian pada Masyarakat Penyandang Difabel di Desa Kacangan Kecamatan Modo Kabupaten Lamongan) - Muhammad Muhaimin; Zamroni Ishaq (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2023)
In essence, people with disabilities or disabilities have the same rights and opportunities in all aspects of life and livelihood, including family matters. Their physical limitations demand that they are always assisted by tools and also humans in everything and work. That is the reason for the researcher to study: 1. what are the efforts made by couples with disabilities to create a sakinah family? 2. What are the factors that support and hinder couples with disabilities to maintain a happy family? This study uses several instruments, including: interviews, observation, documentation. interview. the results of this study are as follows: first, the existence of cooperation in earning a living, educating children, understanding each other's wars, giving each other support, maintaining communication, understanding each other's conditions, and carrying out religious orders are some of the efforts to create a family the sakinah. second, the supporting factor is the support that comes from each partner, family and community environment. While the inhibiting factors are the lack of employment and erratic income, the application of parenting patterns for children that is less than optimal due to the physical limitations of disabled couples..